PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI DENGAN METODE EDUTAINMENT DI MAS TAHFIZIL QURAN - Nurul Kusuma Wardani (Universitas Negeri Medan, 2019)
Abstract The underlying problem of this research was the low ability of students’ in writing narrative. This was caused by the lack of interest of students’ in following the lesson and the lack of creativity of teachers when used the method of learning, so that students’ have difficulty in following the learning of writing narrative. This study aims to determine the improvement of writing narrative ability with the application of edutainment method in the students’ of class VII.2 MTs Nujumul Huda Batu Samban in Academic Year 2016/2017. This research was Classroom Action Research consisting of two cycles. Each cycle consists of the planning stage, the action planning stage, the observation and evaluation phase, and the reflection stage. Data collection methods were used observation methods, test methods (in the form of writing narrative assignments), and documentation methods. The collected data were analyzed used qualitative and quantitative data analysis. Based on the results of the learning process obtained results as follows. The results of the increase in teacher activity cycle I reached 90.28% increased to 94.44% in cycle II. In the first cycle students’ learning activity that was 87.72% increased to 90.28% in cycle II. Students’ learning outcomes also increased. The average learning achievement of students’ in the first cycle reached 66.77 increased to 73.37 in cycle II with learning completeness reached 87.09%. Thus it should be concluded that the used of edutainment method can improve the ability of writing narrative essay for the students. Keywords: Writing, Essay, Narrative, Edutainment Method